INNOVATION IN HIGHER EDUCATION. AN EXPERIENCE OF INTERNATIONAL COLLABORATION - SOARES, K. C.; MEGIBOW, JON (Revista Brasileira de Administração Política, 2016)
The academic community, in general, is understood to encompass an environment for knowledge acquisition, supportive of research into new realms, and the encouragement of learning. The “oratory” means of conveying knowledge with one person speaking and others listening — created the basis for the “lecturing” approach to transmitting knowledge. In the twentieth century, “field trips” were an opportunity for “getting out” of the formal classroom and for learning in other environments. The industrial and education fields have long believed in and utilized the “apprenticeship” system and approach to learning. Laboratory experiences have dominated the biology, chemistry, and physics classrooms and more recently many of these experiences have been extended to field activities, outside of the formal classroom/school environment.